Implementasi Budaya Religius Dalam Pembentukan Karakter Disiplin Peserta Didik Di SMAN 2 Bengkalis - Yanti , Selvi; Sarmila, Sarmila; Nuriyati , Tuty (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This research investigates how the implementation of religious culture contributes to the development of students’ disciplinary character at SMAN 2 Bengkalis. It aims to explore how the application of religious culture influences the formation of students’ discipline. The research methodology employed is descriptive qualitative, focusing on the students of iSMAN 2 Bengkalis as the primary subjects. Data collection techniques included observation, interviews, and documentation, while data analysis involved data reduction, data display, and drawing conclusions. The validity of the data was ensured by comparing the findings from observations and interviews. The study’s findings ievealed that students can cultivate a disciplinary character through the integration of religious culture into their daily lives at school. To foster discipline, SMAN 2 Bengkalis students practice various religious rituals, such as exchanging greetings before classes, engaging in prayers before studying, reciting the Qur’an (tadarus), congregational prayers during Dhuhr, and participating in collective acts of charity and group readings of the Yasin every Friday morning